Determinant Factors of Service Quality for Green Logistics Service Providers of Cross-Border Trade In Thailand - Booyarit. P., Pichit, P., Utayartana, N.,; Mustakim, M., Abaidullah, M., (Opción, 1970)
Logistics service providers in Thailand provide transportation and warehousing services for cross-border trade activities between Thailand and neighbouring countries namely Malaysia, Laos, Cambodia and Myanmar. The objective of this research is to investigate the service quality of green logistics practices among the services of cross-border in Thailand. Environmental friendly in logistics is inevitable due to the global campaign in supporting on a sustainable cross-border logistics. Logistics service providers in Thailand need to put an effort in providing Green Logistics practices to their customers. Green logistics involves the uses of environmental friendly of transportation and warehousing in using biofuel, renewable energy sources in reduction of wastes, better atmospheric emissions, permissible noises and encouraged safety. The respondents of this research were 384 of logistics service providers located at cross border areas of Malaysia, Laos, Cambodia and Myanmar. Stratified random sampling is used on samples through the structured questionnaires and regression also applied for data analysis procedures. Finding of this research revealed that by practicing on green and service quality will improve on the logistics performance as well as quality of the overall logistics businesses. It also suggests that the logistics service providers should deliver on the Green Quality at cross-border trade activities. This research is able to support on logistics providers and understand on the importance of green logistics service quality for better business performance in future